EXAMINING TEACHERS’ PERCEPTIONS AND ATTITUDES TOWARDS THE INTEGRATION OF TECHNOLOGY IN ASSESSMENT PRACTICES - Indayani, Wahyu Restu; Asari, Slamet; Maruf, Nirwanto (University of Kuningan, 2023)
The integration of technology in education has become increasingly important, and understanding how teachers perceive and approach online assessment is crucial for effective implementation in the field of EFL teaching. This study investigates the perceptions and attitudes of EFL teachers in Junior High Schools in East Java towards online assessment. Despite the potential benefits of online assessment, there is a research gap in how EFL teachers in this context perceive and utilize it. This research aims to explore EFL teachers' beliefs and views about online testing and the specific challenges they encounter when adopting online assessment. Employing a mixed-methods approach, data were gathered from 100 EFL teachers through surveys and semi-structured interviews. Findings reveal that EFL teachers generally hold a positive perception and attitude towards online assessment, acknowledging advantages like faster grading and accurate measurement of learning outcomes. However, they face challenges related to technological proficiency, student competence assessment, and teacher confidence in using ICT. These findings contribute to the field by emphasizing the importance of supporting teachers' technological proficiency and fostering an inclusive learning environment, optimizing the potential benefits of online assessment in EFL classrooms.